(untitled) (CSIAM Transactions on Life Sciences, 2025)
In this paper, we propose an age-structured epidemic model with strain mutation and age-based vaccination. We define the reproduction numbers of both the original and mutant strains (R_0^1 and R_0^2). If the reproduction number R_0 < 1, the disease-free steady state is locally asymptotically stable. If the reproduction number R_0^2 > 1, there exists a dominant steady state of the mutant strain. Conditions for local stability of this dominant steady state are also obtained. If both reproduction numbers R_0^1 and R_0^2 are greater than 1, a coexistence steady state may occur. Finally, the uniform persistence of the disease described by our age-structured model is strictly proved when the reproduction number R_0^1 > 1. By using the data of the COVID-19 epidemic in Wuhan and the theoretical results obtained in this paper, some numerical calculations are carried out to demonstrate the effect of the age-based vaccination strategy.